Assessing the utility of in vitro microtubule assays for studying mechanisms of peripheral neuropathy with the microtubule inhibitor class of cancer chemotherapy. (5th January 2020) - Genualdi, C.; Feinstein, S.C.; Wilson, L.; Jordan, M.A.; Stagg, N.J.
Abstract: The microtubule inhibitor (MTI) class of chemotherapeutics provide an effective treatment for several different types of cancers, however, severe chemotherapy-induced peripheral neuropathy (CIPN) is a major dose limiting toxicity in patients that limits their use. While CIPN was predicted with MTIs based on histopathology and functional effects in non-clinical toxicology studies, these investigations often require large numbers of animals and long term studies. As in vitro MT assays have been used for decades to study mechanisms of efficacy, we hypothesized that those same assays could be used to study mechanisms of peripheral neuropathy and predict severe CIPN. We analyzed published data on in vitro microtubule (MT) properties for different MTIs that cause varying levels of peripheral neuropathy in patients. Eribulin, vinorelbine and vinfluinine, which all have less severe CIPN than the vinca alkaloids or taxanes, have unique MT properties consisting of reduced affinity and limited binding to MTs (i.e. bind only to the ends and not along the length). Binding more potently to tubulin in the absence of neuronal BIII tubulin was also observed with eribulin and may suggest specificity for tumor tubulin over neuronal tubulin. These are possible mechanisms for causing less severe deleterious effects on MTs in peripheral nerves leading to reduced severity of CIPN. Our analyses demonstrated that in vitro tools used to study the mechanisms of action in inducing severe CIPN (i.e MTI interactions with MTs) warrant further investigation and may be useful for developing next generation MTIs with reduced CIPN. Highlights: In vitro MT properties (binding and dynamicity) have been assessed for many MTIs. MTI's with less severe CIPN have reduced in vitro MT affinity and binding. An MTI with less severe CIPN also had more MT binding in absence of neuronal MTs. In vitro MT properties may be used to develop MTIs with less severe CIPN.